The new patient and responsible self-medication practices: A critical review - Talevi, Alan (2010)
Due to a wide range of factors, such as increasing access to health information and government policies to promote self-care during the past 20-30 years, the “new patient” or ‘expert patient’ has become information strong, information seeking, increasingly demanding (or even aggressive) and skeptical of expert knowledge. This evolution in the patients’ profile has deeply changed the relationship between the patient and the health-care professional and the patients´ self-medication practices. As a result, the classical paternalistic model of health-care professional/patient relationship has shown its limitations, and new models have been proposed and adopted in the health-care community. In this paper, we have carefully analyzed the causes behind the changes in the patients´ behavior and their consequences on the self-medication phenomena, and discuss which of the known models of patient/health-care professional relationship (from the paternalistic to the deliberative model) should be adopted in order to move forward to responsible self-medication conducts.